Possible Roles of the AP-1 Site in the Cytosolic T3 Binding Protein Promoter and Insights into its Physiological Significance - Suzuki, S.; Nishio, S.-I.; Ishii, H.; Sekido, T.; Takeshige, K.; Ohkubo, Y.; Hiwatashi, D.; Takeda, T.; Komatsu, M. (Hormone and Metabolic Research, 2013)
Cytosolic 3,5,3′-triiodo-l-thyronine-binding protein plays pivotal roles in the regulation of intracellular 3,5,3′-triiodo-l-thyronine concentration in vivo. The expression of the protein, which is identical to μ-crystallin, is regulated by various factors. To elucidate the mechanisms of its expression, we evaluated the promoter transactivity and insulin signaling via the AP-1 site in the promoter. The isolated 600 bp human and 1976 bp mouse 5′-flanking regions were cloned in a luciferase reporter plasmid. The luciferase activity was estimated in GH3, dRLh-84, HEK293, and insulin receptor-overexpressing CHO-IR cells. The effects of 12-O-tetradecanoylphorbol 13-acetate and insulin on μ-crystallin mRNA expression were evaluated in various cells. The region between −200 and the transcriptional start site was crucial for constitutive expression in μ-crystallin-expressing dRLh-84 cells. This region contained an AP-1 site. 12-O-Tetradecanoylphorbol 13-acetate increased the level of μ-crystallin mRNA expression in HEK 293 cells. The compound also increased luciferase activity through the promoter. Mutation in the AP1 site diminished the response to the compound. The promoter was also activated by insulin treatment in CHO-IR cells. Insulin treatment increased μ-crystallin mRNA expression in Raw264.7 cells, but decreased in HEK293, P19, and dRLH-84 cells. The expression of μ-crystallin was regulated through the AP-1 site in the promoter. The signals related to AP-1 activation, such as insulin signaling may have diverse effects on μ-crystallin mRNA expression.
Keywords: TPA; thyroid hormone; binding protein; insulin; gene expression